EROSI KEPERCAYAAN PUBLIK TERHADAP KADER PARTAI POLITIK DI ERA POLITIK DIGITAL: ANTARA REPRESENTASI DAN PENCITRAAN - Maria Gabriel Oktriana Tangkas; Yosefina Simanjuntak; Anjuwita Putri Adela Nababan; Christina Kenika Br. Keliat; Prawira Wibawa H; Parlaungan Gabriel Siahaan (STKIP Subang, 2026)
This study examines the erosion of public trust in political party cadres in the era of digital politics, where social media has become a dominant platform for political communication. Political parties increasingly utilize digital media for image building, branding, and influencing public opinion. However, excessive political imaging often creates a gap between public expectations and actual political representation. This study aims to analyze the influence of digital political communication on declining public trust in political parties. Using a qualitative library research approach, data were collected from books, journals, articles, and related documents. The findings show that public trust has declined due to political imaging, disinformation, propaganda, low digital literacy, and political polarization. Consequently, political parties tend to prioritize popularity and electability over substantive public representation.